В нашу гавань заходили корабли: песни / составители Э. Н. Успенский Э. Н. Филина - Успенский Эдуард Николаевич (ОМЕГА, 1995)
Экземпляры: аб. (1997) / Инвентарный номер: 39672 / Цена: / Сис.шифр: 85.94 / Авт.знак: В 11 / ГРНТИ: 18.41.51 / ББК: 85.94